Intracellular Staphylococcus aureus inhibits autophagy of bovine mammary epithelial cells through activating p38α. Issue 3 (August 2021) - Wang, Run; Zhang, Wen; Wang, Lumei; Geng, Na; Wang, Xiaozhou; Zhang, Meihua; Liu, Jianzhu; Liu, Yongxia; Han, Bo
Abstract: Staphylococcus aureus is a common pathogen of bovine mastitis which can induce autophagy and inhibit autophagy flux, resulting in intracellular survival and persistent infection. The aim of the current study was to investigate the role of p38α in the autophagy induced by intracellular S. aureus in bovine mammary epithelial cells. An intracellular infection model of MAC-T cells was constructed, and activation of p38α was examined after S. aureus invasion. Through activating/inhibiting p38α by anisomycin/SB203580, the autophagosomes, LC3 and p62 level were analyzed by immunofluorescence and western blot. To further study the detailed mechanism of p38α, phosphorylation of ULK1ser757 was also detected. The results showed that intracellular S. aureus activated p38α, and the activation developed in a time-dependent manner. Inhibition of p38α promoted intracellular S. aureus -induced autophagy flow, up-regulated the ratio of LC3 II/I, reduced the level of p62 and inhibited the phosphorylation of ULK1ser757, whereas the above results were reversed after activation of p38α. The current study indicated that intracellular S. aureus can inhibit autophagy flow by activating p38α in bovine mammary epithelial cells.